2017
DOI: 10.1002/adfm.201604214
|View full text |Cite
|
Sign up to set email alerts
|

Kirigami/Origami‐Based Soft Deployable Reflector for Optical Beam Steering

Abstract: The beam steering mechanism has been a key element for various applications ranging from sensing and imaging to solar tracking systems. However, conventional beam steering systems are bulky and complex and present significant challenges for scaling up. This work introduces the use of soft deployable reflectors combining a soft deployable structure with simple kirigami/origami reflective films. This structure can be used as a macroscale beam steering mechanism that is both simple and compact. This work first de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 25 publications
0
44
0
Order By: Relevance
“…We further explored possible applications for the above‐mentioned structures as tunable optical transmission and reflection systems. [27,53,54] For these experiments, we incorporated fluorescence nanoparticles within the PDMS matrix and performed fluorescence microscopy (at varying mismatch strains) to compare luminescence profiles, as demonstrated in Figure . A high luminescence value refers to an elevated level of optical reflection while a low luminescence value means that the particular sample is primarily transmitting the incident light.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further explored possible applications for the above‐mentioned structures as tunable optical transmission and reflection systems. [27,53,54] For these experiments, we incorporated fluorescence nanoparticles within the PDMS matrix and performed fluorescence microscopy (at varying mismatch strains) to compare luminescence profiles, as demonstrated in Figure . A high luminescence value refers to an elevated level of optical reflection while a low luminescence value means that the particular sample is primarily transmitting the incident light.…”
Section: Resultsmentioning
confidence: 99%
“…In an effort to resolve the above‐mentioned problems, here we report the programmable and on‐demand generation of complex 3D shapes from hinge‐less planar bilayers incorporating Kirigami cuts. Kirigami design principles have previously been incorporated into a diverse class of materials to develop mechanical force actuated functional systems for optics,[27,28] actuation,[29] soft robotics,[30] stretchable electronics,[31,32] energy harvesting,[33] reconfigurable metamaterials,[34–36] building skins,[37] and graphene‐based[38] applications. Our goal here is to explore how rational introduction of Kirigami cuts enhances the range of shapes achievable with stimuli‐responsive bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…Dias et al showed that to leading order, the out-of-plane deformation of a single cut is independent of the thickness of the sheet, providing mechanical insight into why this shape changing mechanism can scale down to the thinnest materials [224]. Kirigami-inspired cut patterns have enabled the fabrication of photonic metamaterials [233], metamaterials with tunable material properties [234,11], smart adhesives [235], solar tracking devices [236], stretchable lithium ion batteries [237], optical beam steering [238], shape-shifting structures [239], and ultralightweight linear actuators [224].…”
Section: Origami and Kirigamimentioning
confidence: 99%
“…By exploiting kirigami topologies, a nonstretchable flat sheet can be transformed into an ultrastretchable and conformable structure, while retaining its functional properties. The kirigami approach has been applied across a broad range of length scales, spanning from DNA kirigami at nanoscale, to graphene and nanocomposites at microscale, and various functional materials at macroscale . Another advantage of kirigami is that it could transform a variety of advanced materials and planar systems, that were previously limited in application, into mechanically tunable 2D and 3D architectures with broad geometric diversity .…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of kirigami is that it could transform a variety of advanced materials and planar systems, that were previously limited in application, into mechanically tunable 2D and 3D architectures with broad geometric diversity . Kirigami techniques have been applied in a broad range of areas, including integrated solar tracking, deployable reflectors, energy storage devices, mechanical actuators, sensors, triboelectric nanogenerators, and stretchable electronics, such as conductors, supercapacitors, transistors, and bioprobes, and the stretchability can reach as high as 400% without degradation of intrinsic properties.…”
Section: Introductionmentioning
confidence: 99%